Lexical-Semantic and Etymological Research of Anthroponyms in Uzbek, Russian and English Languages - Koziyeva Iqbol Komiljonovna (Researchparks Publishing, 2021)
Anthroponyms are of great importance in people's lives. They reflected the culture and worldview of society. Names are inextricably linked with the history of the people. This article focuses on lexical-semantic, their origin and etymological research of anthroponyms in Uzbek and Russian languages. Also, anthroponyms are analyzed in examples of Uzbek-Russian surnames.